Penerapan Peraturan Perundang-Undangan Tindak Pidana Kekerasan Seksual di Lingkungan Kampus - Putri Arabella; Linda Tri Wahyuni; Viona Salsabila Avrilyanti; Laksita Sahda Nariswari; Tb. Azril Al Dzikra; Muhammad Rafli Seftian; Ardirahman Daud (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research discusses the negative impact of the internet on society, especially related to cases of sexual violence and revenge porn. Through a descriptive qualitative approach with secondary data analysis, this research highlights a tragic case in Pandeglang, Banten, where a female student, IAK, became a victim of rape and distribution of revenge pornographic content by her ex-boyfriend, Alwi Husein Maolana. This case reflects the complexity of the challenges in dealing with sexual violence in cyberspace, where victims face various forms of physical and psychological violence, as well as threats and blackmail. Even though the perpetrator was punished under the Information and Electronic Transactions Law (UU ITE), there is the potential to charge him with other articles related to sexual violence, rape and coercion. These findings emphasize the need for comprehensive and fair law enforcement in dealing with cybercrime and sexual violence, as well as the importance of deeper awareness and understanding of related legal concepts to protect victims and punish perpetrators appropriately. Thus, this research provides valuable insight into the need for legal reform and public awareness in addressing the negative impact of the internet on sexual violence.